The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5688/ajpe80233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flipped Classroom Design on Student Performance and Perceptions in a Pharmacotherapy Course

Abstract: Objective. To determine whether a flipped classroom design would improve student performance and perceptions of the learning experience compared to traditional lecture course design in a required pharmacotherapy course for second-year pharmacy students. Design. Students viewed short online videos about the foundational concepts and answered selfassessment questions prior to face-to-face sessions involving patient case discussions. Assessment. Pretest/posttest and precourse/postcourse surveys evaluated students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 31 publications
(40 reference statements)
14
119
2
4
Order By: Relevance
“…5 Existing literature, although limited, suggests that flipping a class requires considerably more faculty time and resources in order to be effectively delivered. 5,7 McLaughlin and colleagues estimated that in order to "flip" a class, a professor would have to invest 127% more time for course development and management. After initial development, the same group found that after the initial development time, the flipped classroom requires 57% more time to maintain compared to a lecture course.…”
Section: Introductionmentioning
confidence: 99%
“…5 Existing literature, although limited, suggests that flipping a class requires considerably more faculty time and resources in order to be effectively delivered. 5,7 McLaughlin and colleagues estimated that in order to "flip" a class, a professor would have to invest 127% more time for course development and management. After initial development, the same group found that after the initial development time, the flipped classroom requires 57% more time to maintain compared to a lecture course.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similar results have been established from various studies assessing the impact of flipped educational and assessment models in science and pharmacy undergraduate courses worldwide. 4,7,[10][11][12][13] Despite this growing interest in the flipped classroom approach and the promising results obtained in terms of students' performance and satisfaction in the pharmacy curriculum, 4,[11][12][13] this model has not…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…The time in class is, thus, expended in meaningful discussions, problem solving, and facilitating collaboration among students. 4 Another recent trend comprises the "flipped exam" or "flipped assessment," where students tend to construct their own well-reasoned examinations/assessments utilizing intellectual educational tools provided beforehand. Flipped exams anticipate finding out not only what students know, but also entice thinking in novel ways far from just rehearsing memorized material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been cited in health professional programs such as medicine, nursing, dentistry, and pharmacy [1][2][3][4][5][6][7]. Studies in these fields focus on student perception, satisfaction, and some on academic test scores.…”
Section: The Flipped Classroom In Health Professional Schoolsmentioning
confidence: 99%